2005
DOI: 10.1097/01.ccx.0000183666.54717.3d
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute renal failure: inherent and modifiable risks

Abstract: There are identified risk factors of acute renal failure. Because acute renal failure is associated with a worsening outcome, particularly if occurring in critical illness and if severe enough to require renal replacement therapy, preventive measures should be part of appropriate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
66
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(80 citation statements)
references
References 53 publications
9
66
0
5
Order By: Relevance
“…This association is most robust among people with eGFR Ͻ45 ml/ min per 1.73 m 2 (3). Although CKD is a widely known risk factor for acute renal failure (ARF; also known as acute kidney injury [AKI]) (4,5), surprisingly little is known about clinical outcomes, especially long-term outcomes, among patients who have CKD and experience superimposed ARF (acute on chronic renal failure). Most published studies about ARF have focused exclusively on in-hospital outcomes with often scant, if any, follow-up after discharge.…”
mentioning
confidence: 99%
“…This association is most robust among people with eGFR Ͻ45 ml/ min per 1.73 m 2 (3). Although CKD is a widely known risk factor for acute renal failure (ARF; also known as acute kidney injury [AKI]) (4,5), surprisingly little is known about clinical outcomes, especially long-term outcomes, among patients who have CKD and experience superimposed ARF (acute on chronic renal failure). Most published studies about ARF have focused exclusively on in-hospital outcomes with often scant, if any, follow-up after discharge.…”
mentioning
confidence: 99%
“…In addition, diabetes is a generally recognized risk factor for AKI in several settings. 10 Hyperglycemia and insulin resistance are also common in critically ill patients, even in those without diabetes, 11,12 and are associated with increased morbidity and mortality. [13][14][15][16][17][18][19] Observational trials, after correction for diabetes and other known risk factors, have shown an association between pre-or intraoperative hyperglycemia and postoperative AKI after cardiac surgery, 20,21 between hyperglycemia at cardiac catheterization and contrast nephropathy, 22 and between hyperglycemia during total parenteral nutrition and the development of AKI.…”
mentioning
confidence: 99%
“…La importancia de la caída en la presión de perfusión renal como mecanismo de IRA ha sido destacada previamente por otros autores 16,17 . En particular, el estudio de Chvojka et al 16 muestra que en animales sépticos, la existencia de IRA se correlacionó principalmente a una disminución en la presión de perfusión renal.…”
Section: Discussionunclassified